Evaluation of Electrical Harmonics in Building Installations - Rizky Aprylianto Susilo; Tolanda, Fransiskus Sandi; Hidayat, Arif; Handriano, Patrik; Amalia, Vita; Ita Basari, Besse (Emitor: Jurnal Teknik Elektro, 2024)
This study aims to determine the level of harmonics, and conduct harmonic analysis on the electrical system in the new Building of the Information Technology Department of Samarinda State Polytechnic. Harmonics are electric waves that have frequencies with multiples of the base frequency of the power source (50 Hz in Indonesia). Harmonics can arise due to the use of electronic equipment that has non-linear load properties. This is becoming a major problem for power quality issues and harmonic analysis is required to scrutinize in component modeling to minimize or eliminate these harmonic disturbances. Based on research that the harmonic content in the new building of the Information Technology Department of Samarinda State Polytechnic has not met the standards. In this case, the power quality in such buildings exceeds the specified standards. The method used is the design of passive filter simulation in distribution transformers using ETAP  software. The result of this study is a decrease in harmonic currents after installing a passive filter with an initial THDi value in phase S of 59.84% for IHDi values in the 5th order of 57.25% the value does not meet IEEE 519-2014 standards, the use of single-tuned passive filters can reduce the THDi content in phase S to 10.94% and the 5th order phase S down to 10.46 already meets IEEE 519 – 2014 standards, namely THDi 15% and IHDi in the 5th order 12% with SCRatio between 100-1000 A.